A bioturbation classification of European marine infaunal invertebrates. Issue 11 (17th September 2013) - Queirós, Ana M.; Birchenough, Silvana N. R.; Bremner, Julie; Godbold, Jasmin A.; Parker, Ruth E.; Romero‐Ramirez, Alicia; Reiss, Henning; Solan, Martin; Somerfield, Paul J.; Van, Carl; Van, Gert; Widdicombe, Stephen
Abstract Bioturbation, the biogenic modification of sediments through particle reworking and burrow ventilation, is a key mediator of many important geochemical processes in marine systems. In situ quantification of bioturbation can be achieved in a myriad of ways, requiring expert knowledge, technology, and resources not always available, and not feasible in some settings. Where dedicated research programmes do not exist, a practical alternative is the adoption of a trait‐based approach to estimate community bioturbation potential (BPc). This index can be calculated from inventories of species, abundance and biomass data (routinely available for many systems), and a functional classification of organism traits associated with sediment mixing (less available). Presently, however, there is no agreed standard categorization for the reworking mode and mobility of benthic species. Based on information from the literature and expert opinion, we provide a functional classification for 1033 benthic invertebrate species from the northwest European continental shelf, as a tool to enable the standardized calculation of BPc in the region. Future uses of this classification table will increase the comparability and utility of large‐scale assessments of ecosystem processes and functioning influenced by bioturbation (e.g., to support legislation). The key strengths, assumptions, and limitations of BPc as a metric are critically reviewed, offering guidelines for its calculation and application.